Piezoelectric hydrogel, preparation method thereof and ultrasonic treatment device
By developing an injectable piezoelectric hydrogel containing methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin, and glycerin, combined with an ultrasonic therapeutic device, the problem of excessive drug release in periodontitis treatment was solved and problems with unsatisfactory treatment effects, it achieves deep delivery of drugs and relieves inflammation, and promotes the regeneration of periodontal tissue.
Patent Information
- Application Number
- CN202411259617.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
AI Technical Summary
The existing local drug delivery system for periodontitis treatment has problems such as low bioavailability, too fast drug release and unsatisfactory treatment effect.
The development of an injectedococcom water gel contains methyl acrylic, zinc oxide nanoparticles, puerariain, and glycerin, which combines ultrasonic device combined with ultrasound to achieve deep delivery and slow release of drugs.
It improves the effect and quality of periodontitis treatment, achieves accurate delivery of drugs and relieves inflammation through injectable hydrogel, and promotes the regeneration of periodontal tissue.
Smart Images

Figure CN119345353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, and in particular to a piezoelectric hydrogel and a preparation method thereof, and an ultrasonic treatment device. Background Art
[0002] Periodontitis is a chronic inflammatory disease that causes destruction of tooth-supporting tissues due to a variety of reasons, such as dental plaque microorganisms and oral environmental factors. The disease has a very high prevalence in the population, and its pathogenesis includes multiple risk factors such as smoking, hypertension, psychological stress, and systemic diseases. If not treated in time, it can lead to damage to periodontal tissues, loss of alveolar bone, and ultimately loosening and loss of teeth. The current goal of periodontitis treatment is to prevent disease progression, alleviate clinical symptoms, promote recovery of damaged periodontal tissues, and help patients maintain a healthy periodontal state.
[0003] In recent years, in order to achieve better treatment effects, people have begun to use periodontal local drug delivery systems for the treatment of periodontitis. This treatment mode is flexible and the dosage management is simple. It can reduce the dosage and frequency of administration and improve patient compliance. However, these systems also have some disadvantages, such as low bioavailability, too fast drug release rate, and unsatisfactory treatment effect. Therefore, it is very important to develop a local drug delivery sustained-release system that can improve the quality and effect of periodontitis treatment.
[0004] Hydrogel is a cross-linked semisolid system that can evenly disperse active drug molecules in a solid medium. It does not flow in steady state, so it can quickly fill tissue defects and is easy to use. Hydrogels have attracted much attention due to their excellent water absorption, adjustability (such as physical, chemical and biocompatibility) and drug release control. Various natural and synthetic hydrogels have been developed to mimic the biological properties of natural extracellular matrix, which helps promote cell implantation, adhesion and growth. Although the drug is released quickly in hydrogels, it has strong bioadhesion, is easy to manufacture and administer, has the characteristics of drug sustained release mode, minimum dosage frequency and low drug toxicity, can reduce local irritation and host immune response, and can be eliminated through normal catabolic pathways. Therefore, hydrogels have broad application prospects in the local delivery of periodontal drugs.
[0005] However, traditional hydrogel materials are mainly used in in vitro scenarios due to their uncertain biocompatibility and biosafety. Summary of the invention
[0006] Based on this, it is necessary to provide an injectable piezoelectric hydrogel suitable for the treatment of periodontitis, a preparation method thereof, and an ultrasonic treatment device.
[0007] A piezoelectric hydrogel comprises methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin and glycerol, wherein the silver-loaded zinc oxide nanoparticles, puerarin and glycerol are dispersed in the methacrylated gelatin.
[0008] In the piezoelectric hydrogel of the technical solution of the present invention, methacrylated gelatin is used as a hydrogel matrix with a multi-network structure for carrying other functional substances; silver-loaded zinc oxide nanoparticles are used as nanomedicines, and the piezoelectric properties of oral dental bone tissue and the self-powered characteristics of piezoelectric materials such as zinc oxide are used to establish an electric field in situ, thereby achieving the purpose of stimulating bone tissue regeneration. Silver ions have a strong antibacterial effect on Porphyromonas gingivalis. At the same time, under the action of ultrasound, it can not only enhance the permeability of oral tissue, so that the drug penetrates into the deep tissue and improves the efficacy of the drug, but also ultrasound can induce zinc oxide to generate a large amount of active oxygen, which can be used as a bactericide, which is very important for the treatment of bacterial infectious diseases such as periodontitis; at the same time, the addition of puerarin gives the hydrogel anti-inflammatory and anti-bone resorption functions, which helps to reduce inflammatory reactions and protect the health of periodontal tissues; the addition of glycerol improves the fluidity and moisture retention of the hydrogel, making the hydrogel easier to inject into the treatment site while maintaining the stability of the drug. This multifunctional piezoelectric hydrogel can make up for the shortcomings of a single component in performance, thereby improving the comprehensiveness and effect of the treatment, and is suitable for the treatment of periodontitis. Furthermore, the piezoelectric hydrogel is injectable and can accurately deliver drugs to the affected area, quickly relieve inflammation, and promote the regeneration of periodontal tissue. This injectability makes treatment more convenient and precise, helps to improve the patient's treatment experience and accelerate the recovery process.
[0009] In a feasible implementation, the mass ratio of the methacrylated gelatin, the silver-loaded zinc oxide nanoparticles, the puerarin and the glycerol is (50-200):(0.25-1):(0.05-0.2):(10-50).
[0010] In a feasible implementation, in the silver-loaded zinc oxide nanoparticles, nanosilver is coated on the surface of nanozinc oxide, and the mass ratio of the nanosilver to the nanozinc oxide is (1-10):(50-100).
[0011] A method for preparing a piezoelectric hydrogel comprises the following steps:
[0012] Methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol are dissolved in water, mixed evenly and then a photocuring agent is added, mixed evenly and then a cross-linking reaction is carried out, and after sufficient reaction, a piezoelectric hydrogel is obtained.
[0013] The preparation method of the piezoelectric hydrogel of the technical solution of the present invention is simple, and the multifunctional piezoelectric hydrogel prepared can make up for the performance deficiencies of a single component, thereby improving the comprehensiveness and effect of the treatment, and is suitable for the treatment of periodontitis. Furthermore, the piezoelectric hydrogel is injectable, and can accurately deliver drugs to the affected area, quickly relieve inflammation, and promote the regeneration of periodontal tissues. This injectability makes the treatment more convenient and accurate, which helps to improve the patient's treatment experience and accelerate the recovery process.
[0014] In a feasible implementation, the mass ratio of the methacrylated gelatin, the silver-loaded zinc oxide nanoparticles, the puerarin powder and the glycerol is (100-200):(1-5):(0.2-1):(50-100).
[0015] In a feasible implementation, the silver-loaded zinc oxide nanoparticles are prepared by a method comprising the following steps:
[0016] Adding ammonia water dropwise to the silver nitrate solution to obtain a silver ammonia solution after sufficient reaction, and then adding nano zinc oxide powder to obtain a first suspension after sufficient reaction;
[0017] Adding a reducing agent dropwise into the first suspension to obtain a second suspension after sufficient reaction; and
[0018] The second suspension is subjected to solid-liquid separation and the solid is retained, and then dried and ground to obtain silver-loaded zinc oxide nanoparticles.
[0019] In a feasible implementation, the volume ratio of the silver nitrate solution to the ammonia water is (20-40):(3-6), the concentration of the silver nitrate solution is 0.01 mol / L-0.5 mol / L, and the molar concentration of the ammonia water is 25%-28%;
[0020] The ratio of the nano zinc oxide powder to the silver ammonia solution is (0.1 g to 1 g): 20 mL;
[0021] The reducing agent is selected from at least one of a glucose solution and citric acid;
[0022] The concentration of the reducing agent is 0.03 mol / L to 1.5 mol / L, and the volume ratio of the reducing agent to the first suspension is (10 to 20):(20 to 40).
[0023] In a feasible implementation, the methacrylated gelatin is prepared by a method comprising the following steps:
[0024] Dissolving gelatin in water, fully swelling at room temperature and then dissolving at 50°C to 60°C, then dropping methacrylic anhydride and fully reacting at 50°C to 60°C, then adding 30°C to 40°C water to dilute and terminate the reaction, to obtain a methacrylated gelatin solution; and
[0025] The methacrylated gelatin solution is dialyzed at 30° C. to 50° C. to remove unreacted monomers. After the dialysis is completed, the methacrylated gelatin is obtained by vacuum freeze drying.
[0026] In a feasible implementation, methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol are dissolved in water, mixed evenly and then a photocuring agent is added, mixed evenly and then cross-linked, and the piezoelectric hydrogel is obtained after sufficient reaction as follows:
[0027] dissolving methacrylated gelatin in water to obtain a methacrylated gelatin solution;
[0028] adding silver-loaded zinc oxide nanoparticles and puerarin powder into the methacrylated gelatin solution, and mixing them evenly to obtain a first mixed solution;
[0029] Adding glycerol to the first mixed solution, mixing evenly, adding a light curing agent, heating to 35° C. to 45° C. in a light-proof condition and mixing evenly to obtain a second mixed solution; and
[0030] The second mixed solution is subjected to a photo-crosslinking reaction under light-proof conditions, and the piezoelectric hydrogel is obtained after sufficient reaction.
[0031] An ultrasonic therapeutic device comprises the above-mentioned piezoelectric hydrogel and an ultrasonic transducer, wherein the ultrasonic transducer is located on the surface of the piezoelectric hydrogel.
[0032] The ultrasonic treatment device of the technical solution of the present invention combines piezoelectric hydrogel and ultrasound. The ultrasonic transducer is used to provide ultrasound. First, based on the piezoelectric effect, when the piezoelectric material is stimulated by ultrasound, ultrasound will induce mechanical vibration inside the piezoelectric material, separate unpaired electrons and holes, and establish a strong built-in electric field and surface charge. The built-in electric field and surface charge will accelerate the catalytic rate and induce the generation of reactive oxygen, which can quickly kill bacteria; secondly, under ultrasonic irradiation, due to the ultrasonic cavitation effect, the required microbubbles will be generated in the hydrogel. When the microbubbles collapse, a high temperature of more than 5000K and a high pressure of more than 0.5MPa will be generated. The high temperature and high pressure will decompose the water vapor in the bubble to generate hydroxyl free radicals. Hydroxyl free radicals are highly active free radicals with strong oxidizing properties and can effectively kill bacteria. Then, as a drug sustained release system, the piezoelectric hydrogel can not only effectively regulate the sustained release rate of the drug, but also promote the deep release and absorption of the drug, thereby improving the therapeutic effect. Finally, ultrasound is a mechanical energy, and low-intensity pulsed ultrasound can accelerate alveolar bone regeneration and promote the repair and regeneration of periodontal tissue. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Flow chart of a method for preparing a piezoelectric hydrogel according to one embodiment of the present invention;
[0034] Figure 2 The X-ray diffraction pattern of PLA / KNN-PDA prepared in Example 1 of the present invention;
[0035] Figure 3 This is an infrared spectrum of the piezoelectric hydrogel prepared in Example 1 of the present invention;
[0036] Figure 4 This is a scanning electron microscope (SEM) image of the piezoelectric hydrogel prepared in Example 1 of the present invention;
[0037] FIG5(a) and FIG5(b) are phase change diagrams of the piezoelectric hydrogel prepared in Example 1 of the present invention;
[0038] Figure 6 This is a schematic diagram of the injection of the piezoelectric hydrogel prepared in Example 1 of the present invention;
[0039] Figure 7 Comparison of the swelling rates of the piezoelectric hydrogel prepared in Example 1 of the present invention and the GelMa hydrogel prepared in Comparative Example 1;
[0040] Figure 8 The porosity comparison between the piezoelectric hydrogel prepared in Example 1 of the present invention and the GelMa hydrogel prepared in Comparative Example 1;
[0041] Fig. 9The biocompatibility of the piezoelectric hydrogel prepared in Example 1 of the present invention and the GelMa hydrogel prepared in Comparative Example 1 is compared. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] The piezoelectric hydrogel of one embodiment includes methacrylated gelatin (GelMA for short), silver-loaded zinc oxide nanoparticles, puerarin and glycerol, wherein the silver-loaded zinc oxide nanoparticles, puerarin and glycerol are dispersed in the methacrylated gelatin.
[0045] In the piezoelectric hydrogel of this embodiment, methacrylated gelatin is used as a hydrogel matrix having a multi-network structure for carrying other functional substances.
[0046] In the piezoelectric hydrogel of the present embodiment, the nano silver in the silver-loaded zinc oxide nanoparticles (abbreviated as Ag-ZnO nanoparticles) is coated on the surface of nano zinc oxide. As nano drugs, the silver-loaded zinc oxide nanoparticles use the piezoelectric properties of oral dental bone tissue and the self-powered characteristics of piezoelectric materials such as zinc oxide to establish an electric field in situ, thereby achieving the purpose of stimulating bone tissue regeneration. Silver ions have a strong antibacterial effect on Porphyromonas gingivalis. At the same time, under the action of ultrasound, not only can the permeability of oral tissue be enhanced, so that the drug penetrates into the deep tissue and improves the efficacy of the drug, but ultrasound can also induce zinc oxide to generate a large amount of reactive oxygen, which can be used as a bactericide, which is very important for the treatment of bacterial infectious diseases such as periodontitis. Specifically, the release of silver ions is a synergistic oxidation process. As a piezoelectric material, ZnO will generate a built-in electric field under ultrasonic stimulation. This electric field generates more reactive oxygen species (superoxide anions and hydrogen peroxide, etc.) by promoting electron transfer and redox. These reactive oxygen species will gradually convert the single substance Ag into Ag ions. The released Ag ions can interact with the bacterial cell membrane, protein and DNA, destroying the bacterial metabolic activity, and further causing cell damage by promoting the generation of reactive oxygen species (ROS), ultimately achieving an antibacterial effect. This method utilizes the piezoelectric properties of ZnO to effectively control the release rate of Ag ions, thereby improving the antibacterial properties of the material.
[0047] In the piezoelectric hydrogel of this embodiment, the addition of puerarin gives the hydrogel anti-inflammatory and anti-bone resorption functions, which helps to reduce inflammatory reactions and protect the health of periodontal tissues.
[0048] In the piezoelectric hydrogel of this embodiment, the addition of glycerol improves the fluidity and moisture retention of the hydrogel, making the hydrogel easier to inject into the treatment site while maintaining the stability of the drug.
[0049] The piezoelectric hydrogel of this embodiment presents a honeycomb porous structure with a pore size of about 100 microns to 200 microns. The honeycomb porous structure helps to improve the mechanical strength of the hydrogel and also provides a larger specific surface area, which is of great significance for the loading and release of nanomedicines. In addition, this pore size distribution is conducive to cell adhesion and proliferation, making piezoelectric hydrogels have broad application prospects in the fields of tissue engineering and regenerative medicine.
[0050] Based on the aforementioned implementation mode, the mass ratio of methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin and glycerol is (50-200):(0.25-1):(0.05-0.2):(10-50).
[0051] On the basis of the above-mentioned embodiment, in the silver-loaded zinc oxide nanoparticles, nanosilver is coated on the surface of nanozinc oxide, and the mass ratio of nanosilver to nanozinc oxide is (1-10):(50-100).
[0052] The multifunctional piezoelectric hydrogel of the technical solution of the present invention can make up for the shortcomings of a single component in performance, thereby improving the comprehensiveness and effect of the treatment, and is suitable for the treatment of periodontitis. Furthermore, the piezoelectric hydrogel is injectable and can accurately deliver drugs to the affected area, quickly relieve inflammation, and promote the regeneration of periodontal tissue. This injectability makes the treatment more convenient and accurate, helps to improve the patient's treatment experience and accelerate the recovery process.
[0053] See also Figure 1 A method for preparing a piezoelectric hydrogel according to an embodiment of the present invention comprises the following steps:
[0054] S10, dissolving methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol in water, adding a photocuring agent after mixing evenly, performing a cross-linking reaction after mixing evenly, and obtaining a piezoelectric hydrogel after sufficient reaction.
[0055] Based on the aforementioned embodiment, the mass ratio of methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol is (100-200):(1-5):(0.2-1):(50-100).
[0056] Based on the above-mentioned embodiment, silver-loaded zinc oxide nanoparticles are prepared by a method comprising the following steps:
[0057] Adding ammonia water dropwise to the silver nitrate solution to obtain a silver ammonia solution after sufficient reaction, and then adding nano zinc oxide powder to obtain a first suspension after sufficient reaction;
[0058] Adding a reducing agent dropwise into the first suspension to obtain a second suspension after sufficient reaction; and
[0059] The second suspension is subjected to solid-liquid separation and the solid is retained, and then dried and ground to obtain silver-loaded zinc oxide nanoparticles.
[0060] On the basis of the above-mentioned implementation mode, the volume ratio of silver nitrate solution to ammonia water is (20-40):(3-6), the concentration of silver nitrate solution is 0.01 mol / L-0.5 mol / L, and the molar concentration of ammonia water is 25%-28%.
[0061] On the basis of the above-mentioned implementation mode, the ratio of nano zinc oxide powder to silver ammonia solution is (0.1 g to 1 g): 20 mL.
[0062] Based on the above embodiment, the reducing agent is selected from at least one of glucose solution and citric acid.
[0063] Based on the above-mentioned embodiment, the concentration of the reducing agent is 0.03 mol / L to 1.5 mol / L, and the volume ratio of the reducing agent to the first suspension is (10 to 20):(20 to 40).
[0064] Based on the above-mentioned embodiment, methacrylated gelatin is prepared by a method comprising the following steps:
[0065] Dissolving gelatin in water, fully swelling at room temperature and then dissolving at 50°C to 60°C, then dropping methacrylic anhydride and fully reacting at 50°C to 60°C, then adding 30°C to 40°C water to dilute and terminate the reaction, to obtain a methacrylated gelatin solution; and
[0066] The methacrylated gelatin solution is dialyzed at 30°C to 50°C to remove unreacted monomers. After the dialysis is completed, the methacrylated gelatin is obtained by vacuum freeze drying.
[0067] On the basis of the above-mentioned embodiment, methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol are dissolved in water, mixed evenly and then a photocuring agent is added, mixed evenly and then a cross-linking reaction is performed, and the operation of obtaining a piezoelectric hydrogel after sufficient reaction is as follows:
[0068] dissolving methacrylated gelatin in water to obtain a methacrylated gelatin solution;
[0069] adding silver-loaded zinc oxide nanoparticles and puerarin powder into the methacrylated gelatin solution, and mixing them evenly to obtain a first mixed solution;
[0070] Adding glycerol to the first mixed solution, mixing evenly, adding a light curing agent, heating to 35° C. to 45° C. in a light-proof condition and mixing evenly to obtain a second mixed solution; and
[0071] The second mixed solution is subjected to a photo-crosslinking reaction under light-proof conditions, and the piezoelectric hydrogel is obtained after sufficient reaction.
[0072] The photocuring agent may be LAP, 2959 or TPO. The photocrosslinking reaction of the second mixed solution under light-proof conditions refers to the photocrosslinking reaction of the second mixed solution under light-proof conditions, which is to be irradiated with ultraviolet light under light-proof conditions except for the light required for the photocrosslinking.
[0073] The preparation method of the piezoelectric hydrogel of the technical solution of the present invention is simple, and the multifunctional piezoelectric hydrogel prepared can make up for the performance deficiencies of a single component, thereby improving the comprehensiveness and effect of the treatment, and is suitable for the treatment of periodontitis. Furthermore, the piezoelectric hydrogel is injectable, and can accurately deliver drugs to the affected area, quickly relieve inflammation, and promote the regeneration of periodontal tissues. This injectability makes the treatment more convenient and accurate, which helps to improve the patient's treatment experience and accelerate the recovery process.
[0074] An ultrasonic therapeutic device of one embodiment includes any of the above-mentioned piezoelectric hydrogels and an ultrasonic transducer, wherein the ultrasonic transducer is located on the surface of the piezoelectric hydrogel. Specifically, the ultrasonic transducer and the piezoelectric hydrogel are adhered together by a backing tape, and an isolation layer is provided on the side of the piezoelectric hydrogel away from the ultrasonic transducer for protection. When it is needed, the isolation layer is removed, and the piezoelectric hydrogel side of the ultrasonic therapeutic device is attached to the desired treatment part of the body, such as the location of an epidermal wound.
[0075] The ultrasonic treatment device of the technical solution of the present invention combines piezoelectric hydrogel and ultrasound. The ultrasonic transducer is used to provide ultrasound. First, based on the piezoelectric effect, when the piezoelectric material is stimulated by ultrasound, ultrasound will induce mechanical vibration inside the piezoelectric material, separate unpaired electrons and holes, and establish a strong built-in electric field and surface charge. The built-in electric field and surface charge will accelerate the catalytic rate and induce the generation of reactive oxygen, which can quickly kill bacteria; secondly, under ultrasonic irradiation, due to the ultrasonic cavitation effect, the required microbubbles will be generated in the hydrogel. When the microbubbles collapse, a high temperature of more than 5000K and a high pressure of more than 0.5MPa will be generated. The high temperature and high pressure will decompose the water vapor in the bubble to generate hydroxyl free radicals. Hydroxyl free radicals are highly active free radicals with strong oxidizing properties and can effectively kill bacteria. Then, as a drug sustained release system, the piezoelectric hydrogel can not only effectively regulate the sustained release rate of the drug, but also promote the deep release and absorption of the drug, thereby improving the therapeutic effect. Finally, ultrasound is a mechanical energy, and low-intensity pulsed ultrasound can accelerate alveolar bone regeneration and promote the repair and regeneration of periodontal tissue.
[0076] With reference to the above implementation contents, in order to make the technical solution of the present invention more specific, clear and easy to understand, the technical solution of the present invention is now exemplified. However, it should be noted that the contents to be protected by the present invention are not limited to the following embodiments.
[0077] Example 1
[0078] Embodiment 1 provides a piezoelectric hydrogel and a preparation method thereof, comprising the following steps:
[0079] 1. Synthesis of silver-loaded zinc oxide nanoparticles (Ag-ZnO nanoparticles for short)
[0080] Step 1.1: Add 28% ammonia water to 0.5 mol / L silver nitrate solution, the volume ratio of the silver nitrate solution to the ammonia water is 1:10, to prepare a silver ammonia solution, then weigh 0.1 g of nano ZnO powder on a balance, add it to 20 mL of the silver ammonia solution, stir and react for 1 hour, and obtain a first suspension;
[0081] Step 1.2: Prepare 20 mL of 2 mol / L glucose solution, add it dropwise into the first suspension, continue stirring and reacting for 1 hour, and obtain a second suspension;
[0082] Step 1.3: Pour the second suspension into a centrifuge tube, collect the solid product with a high-speed centrifuge, and then repeatedly rinse it with deionized water, and put the product into an oven and dry it at a constant temperature of 60°C for 8 hours, and finally grind the dried product with a mortar for 20 minutes to obtain Ag-ZnO nanoparticles.
[0083] 2. Synthesis of Gelatin Methacrylate (GelMA)
[0084] Step 2.1: Dissolve 10 g of gelatin (manufacturer: Merck Sigma) in 200 mL of 40°C deionized water and swell at room temperature for 2 hours;
[0085] Step 2.2: Stir and dissolve at 60°C for 2 hours, then slowly drop 8 mL of methacrylic anhydride, react at 60°C for 6 hours with continuous stirring;
[0086] Step 2.3: Add 200 mL of 40° C. deionized water to dilute and terminate the reaction to obtain a methacrylated gelatin solution;
[0087] Step 2.4: The methacrylated gelatin solution is then placed in a dialysis bag (molecular weight of 8000-14000), and the dialysis bag is placed in deionized water at 45°C for 5 days to remove unreacted monomers, and the water is changed every 4 hours;
[0088] Step 2.5: Transfer the dialyzed solution to a petri dish to cool, and collect the methacrylated gelatin by vacuum freeze drying.
[0089] 3. Preparation of piezoelectric hydrogel (referred to as Ag-ZnO / Pur / Gl / GelMA)
[0090] Step 3.1: Weigh 0.2 g of GelMA and dissolve it in 2 mL of deionized water to prepare a GelMA solution;
[0091] Step 3.2: Weigh 1 mg of Ag-ZnO nanopowder and 0.5 mg of puerarin powder, add them into the above GelMA solution and stir slowly for 3 hours;
[0092] Step 3.3: Pipette 300 μL of glycerol into the mixture and quickly stir the mixture evenly;
[0093] Step 3.4: Add 6 mg of light curing agent (LAP) and place on a constant temperature shaker at 37°C for about 1 hour in a completely dark environment;
[0094] Step 3.5: Use a disposable sterile medical needle to draw up the mixed solution and add it into a suitable mold;
[0095] Step 3.6: Under the condition of complete light avoidance, irradiate with ultraviolet light to carry out photo-crosslinking reaction, so as to obtain the piezoelectric hydrogel of Example 1.
[0096] Example 2
[0097] 1. Synthesis of silver-loaded zinc oxide nanoparticles (Ag-ZnO nanoparticles for short)
[0098] Step 1.1: Add 28% ammonia water to 0.5 mol / L silver nitrate solution, the volume ratio of the silver nitrate solution to the ammonia water is 1:10, to prepare a silver ammonia solution, then weigh 0.1 g of nano ZnO powder on a balance, add it to 20 mL of the silver ammonia solution, stir and react for 1 hour, and obtain a first suspension;
[0099] Step 1.2: Prepare 20 mL of 2 mol / L glucose solution, add it dropwise into the first suspension, continue stirring and reacting for 1 hour, and obtain a second suspension;
[0100] Step 1.3: Pour the second suspension into a centrifuge tube, collect the solid product with a high-speed centrifuge, and then repeatedly rinse it with deionized water, and put the product into an oven and dry it at a constant temperature of 60°C for 8 hours, and finally grind the dried product with a mortar for 20 minutes to obtain Ag-ZnO nanoparticles.
[0101] 2. Synthesis of Gelatin Methacrylate (GelMA)
[0102] Step 2.1: Dissolve 10 g of gelatin (manufacturer: Merck Sigma) in 200 mL of 40°C deionized water and swell at room temperature for 2 hours;
[0103] Step 2.2: Stir and dissolve at 60°C for 2 hours, then slowly drop 8 mL of methacrylic anhydride, react at 60°C for 6 hours with continuous stirring;
[0104] Step 2.3: Add 200 mL of 40° C. deionized water to dilute and terminate the reaction to obtain a methacrylated gelatin solution;
[0105] Step 2.4: The methacrylated gelatin solution is then placed in a dialysis bag (molecular weight of 8000-14000), and the dialysis bag is placed in deionized water at 45°C for 5 days to remove unreacted monomers, and the water is changed every 4 hours;
[0106] Step 2.5: Transfer the dialyzed solution to a petri dish to cool, and collect the methacrylated gelatin by vacuum freeze drying.
[0107] 3. Preparation of piezoelectric hydrogel (referred to as Ag-ZnO / Pur / Gl / GelMA)
[0108] Step 3.1: Weigh 0.2 g of GelMA and dissolve it in 2 mL of deionized water to prepare a GelMA solution;
[0109] Step 3.2: Weigh 0.5 mg of Ag-ZnO nanopowder and 0.25 mg of puerarin powder, add them into the above GelMA solution and stir slowly for 3 hours;
[0110] Step 3.3: Pipette 150 μL of glycerol into the mixture and quickly stir the mixture evenly;
[0111] Step 3.4: Add 6 mg of light curing agent (LAP) and place on a constant temperature shaker at 37°C for about 1 hour in a completely dark environment;
[0112] Step 3.5: Use a disposable sterile medical needle to draw up the mixed solution and add it into a suitable mold;
[0113] Step 3.6: Under the condition of complete light avoidance, irradiate with ultraviolet light to carry out photo-crosslinking reaction, so as to obtain the piezoelectric hydrogel of Example 2.
[0114] Example 3
[0115] 1. Synthesis of silver-loaded zinc oxide nanoparticles (Ag-ZnO nanoparticles for short)
[0116] Step 1.1: Add 28% ammonia water to 0.5 mol / L silver nitrate solution, the volume ratio of the silver nitrate solution to the ammonia water is 1:10, to prepare a silver ammonia solution, then weigh 0.1 g of nano ZnO powder on a balance, add it to 20 mL of the silver ammonia solution, stir and react for 1 hour, and obtain a first suspension;
[0117] Step 1.2: Prepare 20 mL of 2 mol / L glucose solution, add it dropwise into the first suspension, continue stirring and reacting for 1 hour, and obtain a second suspension;
[0118] Step 1.3: Pour the second suspension into a centrifuge tube, collect the solid product with a high-speed centrifuge, and then repeatedly rinse it with deionized water, and put the product into an oven and dry it at a constant temperature of 60°C for 8 hours, and finally grind the dried product with a mortar for 20 minutes to obtain Ag-ZnO nanoparticles.
[0119] 2. Synthesis of Gelatin Methacrylate (GelMA)
[0120] Step 2.1: Dissolve 10 g of gelatin (manufacturer: Merck Sigma) in 200 mL of 40°C deionized water and swell at room temperature for 2 hours;
[0121] Step 2.2: Stir and dissolve at 60°C for 2 hours, then slowly drop 8 mL of methacrylic anhydride, react at 60°C for 6 hours with continuous stirring;
[0122] Step 2.3: Add 200 mL of 40° C. deionized water to dilute and terminate the reaction to obtain a methacrylated gelatin solution;
[0123] Step 2.4: The methacrylated gelatin solution is then placed in a dialysis bag (molecular weight of 8000-14000), and the dialysis bag is placed in deionized water at 45°C for 5 days to remove unreacted monomers, and the water is changed every 4 hours;
[0124] Step 2.5: Transfer the dialyzed solution to a petri dish to cool, and collect the methacrylated gelatin by vacuum freeze drying.
[0125] 3. Preparation of piezoelectric hydrogel (referred to as Ag-ZnO / Pur / Gl / GelMA)
[0126] Step 3.1: Weigh 0.2 g of GelMA and dissolve it in 2 mL of deionized water to prepare a GelMA solution;
[0127] Step 3.2: Weigh 2 mg of Ag-ZnO nanopowder and 1 mg of puerarin powder, add them to the above GelMA solution and stir slowly for 3 hours;
[0128] Step 3.3: Pipette 300 μL of glycerol into the mixture and quickly stir the mixture evenly;
[0129] Step 3.4: Add 6 mg of light curing agent (LAP) and place on a constant temperature shaker at 37°C for about 1 hour in a completely dark environment;
[0130] Step 3.5: Use a disposable sterile medical needle to draw up the mixed solution and add it into a suitable mold;
[0131] Step 3.6: Under the condition of complete light avoidance, irradiate with ultraviolet light to carry out photo-crosslinking reaction, thereby obtaining the piezoelectric hydrogel of Example 3.
[0132] Comparative Example 1
[0133] This comparative example is a comparative example of Example 1, and provides a methacrylated gelatin (GelMA for short) and a preparation method thereof, which is exactly the same as the preparation method of GelMA in Example 1.
[0134] Performance Test:
[0135] (1) X-ray diffraction (XRD) test was performed on the Ag-ZnO nanoparticles of Example 1, and the Figure 2 .Will Figure 2 Compared with the XRD standard card PDF2-2004, the peak position of ZnO marked in the figure
[0136] Corresponding to the hexagonal wurtzite structure ZnO, and no other diffraction peaks appear, the lattice constants of the hexagonal wurtzite ZnO are a = 0.3249nm, c = 0.5206nm; Figure 2 The peak positions of Ag marked in the figure correspond to Ag with face-centered cubic structure, whose lattice constants are a=b=c=4.086, α=β=γ=90°, thus it can be determined that the hexagonal wurtzite structured ZnO nanomaterials are successfully prepared. Meanwhile, Ag does not enter the ZnO lattice to change the ZnO crystal structure, but is attached to the surface of ZnO in the form of cubic structured Ag. Moreover, the diffraction peak intensity of Ag is relatively high, and the surface Ag content is relatively high.
[0137] (2) The components of the piezoelectric hydrogel prepared in Example 1 were characterized by Fourier transform infrared spectroscopy (FTIR), and the Figure 3 .from Figure 3 It can be seen that the amide A band peak is at 3280, which is related to the NH stretching vibration; the amide B band peak is at 3072, which is mainly related to the NH stretching vibration; -1 The amide I band is at 1541 cm-1, which is caused by the stretching vibration of C=O. -1 The amide II band peak is at 1235cm, which is the coupling of NH bending vibration and CN stretching vibration; -1 It is the amide III band peak, which originates from the CN stretching vibration and NH bending vibration of the amide bond.
[0138] (3) The piezoelectric hydrogel prepared in Example 1 was characterized by scanning electron microscopy (SEM), and the Figure 4 .Depend on Figure 4It can be seen that the piezoelectric hydrogel prepared in Example 1 presents a honeycomb porous structure with a pore size of about 100 microns to 200 microns. The honeycomb structure helps to improve the mechanical strength of the hydrogel and also provides a larger specific surface area, which is of great significance for the loading and release of nanomedicines. In addition, this pore size distribution is conducive to cell adhesion and proliferation, making piezoelectric hydrogels have broad application prospects in the fields of tissue engineering and regenerative medicine.
[0139] (4) During the preparation process of the piezoelectric hydrogel of Example 1, photographs were taken before and after ultraviolet light irradiation to obtain Figures 5(a) and 5(b), wherein Figure 5(a) is a photograph before ultraviolet light irradiation, and Figure 5(b) is a photograph after ultraviolet light irradiation. It can be seen from Figures 5(a) and 5(b) that after the cross-linking reaction after ultraviolet light irradiation, the sol in the mold is successfully transformed into a gel state. This phase change clearly shows the curing process of the hydrogel under the action of ultraviolet light. Ultraviolet light cross-linking allows the sol to be rapidly transformed into a gel with certain mechanical strength and elasticity, ensuring the shape and structural stability of the piezoelectric hydrogel. This feature is crucial to the ease of operation and reliability of piezoelectric hydrogels in practical applications, and lays the foundation for their wide application in the biomedical field.
[0140] (5) The piezoelectric hydrogel prepared in Example 1 was smoothly injected through a sterile needle. Figure 6 As shown, the injection process was continuously stable without any blockage. This non-blocking injection property greatly improves the convenience and controllability of the hydrogel in practical applications. This property is particularly important when administering drugs in the oral cavity. The structure of the oral region is complex, and conventional drug delivery methods may be limited. The excellent injection performance of the piezoelectric hydrogel prepared in Example 1 enables it to accurately deliver drugs to the target site, thereby improving the therapeutic effect of the drug.
[0141] (6) The piezoelectric hydrogel (Ag-ZnO / Pur / Gl / GelMA) prepared in Example 1 and the GelMA hydrogel of Comparative Example 1 were freeze-dried, and about 100 mg of each sample (denoted as W1) was immersed in a beaker containing 100 mL of phosphate buffer solution at room temperature. The samples were taken out at predetermined time intervals, and the water on the surface of the hydrogel was absorbed by filter paper and then weighed. The weight was represented by W2, according to the formula: Calculate the swelling ratio and get Figure 7 .like Figure 7As shown, the swelling rates of the piezoelectric hydrogel of GelMA in Comparative Example 1 and Example 1 are 492% and 531%, respectively. It can be clearly seen that the swelling performance of the piezoelectric hydrogel of Example 1 is better than that of the GelMA hydrogel in Comparative Example 1, and the improvement in swelling performance is mainly attributed to the addition of glycerol. Glycerol can enhance the fluidity of the gel, thereby promoting more solution to enter the pore structure of the piezoelectric hydrogel. This characteristic not only improves the swelling rate of the piezoelectric hydrogel, but may also have a positive impact on its sustained release behavior as a nano drug carrier.
[0142] (7) Weigh a certain volume of ethanol (recorded as V1), and then soak the GelMA hydrogel prepared in Comparative Example 1 and the piezoelectric hydrogel (Ag-ZnO / Pur / Gl / GelMA) prepared in Example 1 in the ethanol. The total volume of the sample and ethanol is recorded as V2. After soaking for several hours, take out the sample and record the volume at this time (recorded as V3), and then calculate the porosity according to the following formula: get Figure 8 .like Figure 8 As shown, the porosity of the GelMA hydrogel prepared in Comparative Example 1 and the piezoelectric hydrogel prepared in Example 1 are 72.6% and 58.7%, respectively. It can be seen that compared with the GelMA hydrogel in Comparative Example 1, the porosity does decrease after the addition of nanoparticles and glycerol in Example 1. This phenomenon may be due to the fact that the addition of nanoparticles and glycerol changes the internal structure and composition of the hydrogel, making the pores more compact and orderly. Despite the decrease in porosity, this piezoelectric hydrogel may show better performance in terms of mechanical strength and stability, which has a positive impact on its application in fields such as drug delivery and tissue engineering.
[0143] (8) The piezoelectric hydrogel (Ag-ZnO / Pur / Gl / GelMA) prepared in Example 1 and the GelMA in Comparative Example 1 were subjected to a biocompatibility test. The piezoelectric hydrogel in Example 1 and the GelMA in Comparative Example 1 were directly contacted with BMSCs cells to determine the cytotoxicity of the composite hydrogel. Fig. 9 .like Fig. 9 As shown, the GelMa hydrogel of comparative example 1 does not produce cytotoxicity to BMSCs cells and has good biocompatibility; while the piezoelectric hydrogel of Example 1, due to the addition of Ag-ZnO and puerarin, reduces the cell viability of BMSCs to a certain extent. This may be due to the toxicity or inhibitory effect of Ag-ZnO and puerarin on cells, resulting in a decrease in cell viability. Nevertheless, in some special cases, the decrease in cell viability at this ratio may be beneficial. For example, in clinical oral treatment, it may be necessary to produce an appropriate inhibitory effect on periodontal tissue cells.
[0144] (9) The antibacterial activity of the piezoelectric hydrogel prepared in Example 1 against Porphyromonas gingivalis was detected by the inhibition zone method. The specific steps are as follows: 50 μl of Porphyromonas gingivalis (10 6 CFU / mL) were evenly dispersed on the agar plate, the piezoelectric hydrogel was placed in a mold for solidification to obtain a hydrogel material with a diameter of 15 mm, the material was clamped with tweezers and placed on a plate, and ultrasonicated for 10 min respectively. The culture medium was placed in a carbon dioxide incubator at 37.5°C, and the diameter of the inhibition zone was measured after 24 h. The antibacterial performance of the piezoelectric hydrogel was evaluated by comparing the diameters of the inhibition zones. The diameter of the inhibition zone was the average of 3 parallel experiments. The results are shown in Table 1.
[0145] Table 1
[0146] Group Inhibition zone diameter Experiment 1 30.54mm Experiment 2 30.79mm Experiment 3 31.13mm average value 30.82mm
[0147] As can be seen from Table 1, the piezoelectric hydrogel of Example 1 has significant antibacterial activity against Porphyromonas gingivalis, further indicating that it has the possibility of being applied to the treatment of periodontal diseases.
[0148] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0149] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A piezoelectric hydrogel, characterized in that: The piezoelectric hydrogel comprises methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin and glycerol, wherein the silver-loaded zinc oxide nanoparticles, puerarin and glycerol are dispersed in the methacrylated gelatin.
2. The piezoelectric hydrogel according to claim 1, characterized in that: The mass ratio of the methacrylated gelatin, the silver-loaded zinc oxide nanoparticles, the puerarin and the glycerol is (50-200):(0.25-1):(0.05-0.2):(10-50).
3. The piezoelectric hydrogel according to claim 1, characterized in that: In the silver-loaded zinc oxide nanoparticles, nanosilver is coated on the surface of nanozinc oxide, and the mass ratio of the nanosilver to the nanozinc oxide is (1-10):(50-100).
4. A method for preparing a piezoelectric hydrogel, characterized in that: The steps include: Methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol are dissolved in water, mixed evenly and then a photocuring agent is added, mixed evenly and then a cross-linking reaction is carried out, and after sufficient reaction, a piezoelectric hydrogel is obtained.
5. The method for preparing the piezoelectric hydrogel according to claim 4, characterized in that: The mass ratio of the methacrylated gelatin, the silver-loaded zinc oxide nanoparticles, the puerarin powder and the glycerol is (100-200):(1-5):(0.2-1):(50-100).
6. The method for preparing the piezoelectric hydrogel according to claim 4, characterized in that: The silver-loaded zinc oxide nanoparticles are prepared by a method comprising the following steps: Adding ammonia water dropwise to the silver nitrate solution to obtain a silver ammonia solution after sufficient reaction, and then adding nano zinc oxide powder to obtain a first suspension after sufficient reaction; Adding a reducing agent dropwise into the first suspension to obtain a second suspension after sufficient reaction; as well as The second suspension is subjected to solid-liquid separation and the solid is retained, and then dried and ground to obtain silver-loaded zinc oxide nanoparticles.
7. The method for preparing the piezoelectric hydrogel according to claim 6, characterized in that: The volume ratio of the silver nitrate solution to the ammonia water is (20-40):(3-6), the concentration of the silver nitrate solution is 0.01 mol / L-0.5 mol / L, and the molar concentration of the ammonia water is 25%-28%; The ratio of the nano zinc oxide powder to the silver ammonia solution is (0.1 g to 1 g): 20 mL; The reducing agent is selected from at least one of a glucose solution and citric acid; The concentration of the reducing agent is 0.03 mol / L to 1.5 mol / L, and the volume ratio of the reducing agent to the first suspension is (10 to 20):(20 to 40).
8. The method for preparing the piezoelectric hydrogel according to claim 4, characterized in that: The methacrylated gelatin is prepared by a method comprising the following steps: Dissolving gelatin in water, fully swelling at room temperature and then dissolving at 50°C to 60°C, then dropping methacrylic anhydride and fully reacting at 50°C to 60°C, then adding 30°C to 40°C water to dilute and terminate the reaction, to obtain a methacrylated gelatin solution; and The methacrylated gelatin solution is dialyzed at 30° C. to 50° C. to remove unreacted monomers. After the dialysis is completed, the methacrylated gelatin is obtained by vacuum freeze drying.
9. The method for preparing the piezoelectric hydrogel according to claim 4, characterized in that: Methacrylated gelatin, silver-loaded zinc oxide nanoparticles, puerarin powder and glycerol are dissolved in water, mixed evenly and then a photocuring agent is added, mixed evenly and then a cross-linking reaction is performed, and after sufficient reaction, a piezoelectric hydrogel is obtained by the following operation: dissolving methacrylated gelatin in water to obtain a methacrylated gelatin solution; adding silver-loaded zinc oxide nanoparticles and puerarin powder into the methacrylated gelatin solution, and mixing them evenly to obtain a first mixed solution; Adding glycerol to the first mixed solution, mixing evenly, adding a light curing agent, heating to 35° C. to 45° C. in a light-proof condition and mixing evenly to obtain a second mixed solution; and The second mixed solution is subjected to a photo-crosslinking reaction under light-proof conditions, and a piezoelectric hydrogel is obtained after sufficient reaction.
10. An ultrasonic therapeutic device, characterized in that: The invention comprises the piezoelectric hydrogel according to any one of claims 1 to 3 and an ultrasonic transducer, wherein the ultrasonic transducer is located on the surface of the piezoelectric hydrogel.